Well played eaudiobook - DeLuca, Jen (Well Met, 2020)
A laugh-out-loud romantic comedy featuring kilted musicians, Renaissance Faire tavern wenches, and an unlikely love story. LibraryReads Pick   Stacey is jolted when her friends Simon and Emily get engaged. She knew she was putting her life on hold when she stayed in Willow Creek to care for her sick mother, but it's been years now, and even though Stacey loves spending her summers pouring drinks and flirting with patrons at the local Renaissance Faire, she wants more out of life. Stacey vows to have her life figured out by the time her friends get hitched at Faire next summer. Maybe she'll even find The One.   When Stacey imagined "The One," it never occurred to her that her summertime Faire fling, Dex MacLean, might fit the bill. While Dex is easy on the eyes onstage with his band The Dueling Kilts, Stacey has never felt an emotional connection with him. So when she receives a tender email from the typically monosyllabic hunk, she's not sure what to make of it.   Faire returns to Willow Creek, and Stacey comes face-to-face with the man with whom she’s exchanged hundreds of online messages over the past nine months. To Stacey's shock, it isn't Dex—she's been falling in love with a man she barely knows.